Early prelingual auditory and language development in children with simultaneous bilateral and unilateral cochlear implants - Yin, Xiaoling; Gu, Hailing; Kong, Weili; Li, Gang; Zheng, Yun (Frontiers in Pediatrics, 2022)
Purpose This current study aimed to explore early prelingual auditory development (EPLAD) and early language development in Mandarin-speaking children who received simultaneous bilateral cochlear implants (BICI) during the first year of cochlear implantation and compare the performance of the children who received BICI with those received unilateral cochlear implant (UCI). Methods 39 Mandarin-speaking children who received BICIs simultaneously and 36 children with UCIs were enrolled in this study. To access the EPLAD, the Infant-Toddler Meaningful Auditory Integration Scale (IT/MAIS) was conducted, and a subtest of the simplified short-form version of the Mandarin Communicative Development Inventory (SSF-MCDI) was used to evaluate the development of expressive and receptive vocabulary for the children at indicated time points after surgery. Results In both the simultaneous BICI and UCI groups, we observed significantly increased scores of the SSF-MCDI and IT/MAIS 1 year after the surgery. There are indications of early advantages in children with BICI in IT/MAIS scores (at 1, 3, and 6 months after activation). For early development of language, a great difference between the expressive vocabulary scores and the receptive vocabulary scores was observed in both groups. We found there were not significant differences between the two groups on expressive or receptive vocabulary scores, the use of more differentiated measures might be required in future research. We further found that the development of the receptive or expressive vocabulary is dramatically correlated with the age at implantation and the total scores of IT/MAIS for children with simultaneous BICIs. Conclusion These results may supplement the skills development of early language and auditory in Mandarin-native children with simultaneous CIs. It is obvious that children with normal hearing have mastery of receptive vocabulary before that of expressive vocabulary, which is the same as children with unilateral and bilateral CIs in this research. IT/MAIS total scores and age at CI were important factors for early language performance in children with simultaneous BICIs.